Why Korea's globalization policy (1994-1997) failed at localities - Kang, Hee Dong (KDI School, 2000)
Korea’s globalization policy was not as successful in reaching its stated outcomes as was expected in 1994 – 1997. My question about the globalization policy is why the local governments did not manage it proficiently. Local governments developed the organizational infrastructure, human resources, and budgets for its policy. However, many local civil servants, affected by the government’s logic of public relations, were still ambivalent about how to implement the policy because local governments neither directed the civil servants efficiently nor received the necessary autonomy from the central government. The lack of actual recognition of globalization led to its failure as a policy. In particular, the structure of top-down decision-making and lack of autonomy in the organizational management at the local level were the decisive factors leading to the failure of the policy because many local civil servants were not only left outside the decision-makings process but were passive recipients of executive orders. The central government was also responsible for its failure because it should have redistributed the authority and responsibility between the central government and local governments. Such structural reforms should have been focused on developing the civil servants’ ability at all levels. On the basis of the failure of the globalization policy, these methods of reform must be introduced consistently, and the new relationship with the civil groups must be considered seriously for the future.
Thesis(Master) --KDI School:Master of International Relations,2000